Performance of Dufour Effect on Unsteady MHD Flow past through Porous Medium an Exponentially Accelerated Inclined Vertical plate with Variable Temperature and Mass Diffusion - et. al., E. Jothia , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The objective of this study is to the effect of Dufour along unstable MHD stream over an exponentially accelerated started inclined plate through porous medium by variable temperature and mass diffusion. The governing equations occupied in the current study and also the set of non-dimensional partial differential equations are solved by the Laplace-transform technique. The velocity profile , temperature profile, concentration profile have been considered for distinct parameters as warm Grashof value, mass Grashof value, Prandtl value, Dufour value, hypnotic field parameter, Schmidt value and time. The impacts of boundaries are demonstrated graphically for various boundaries. The velocity profiles increases when the value of Dufour value, Magnetic parameter, Schmidt value and also time are decreased and also mass Grashof number, Prandtl number are increased